Complex Incisional Hernias - H Scheuerlein; U Settmacher; M Lenschow; F Rauchfuss (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Incisional hernias are the most frequent "late complications" after laparotomy. They develop in more than 10% of patients and their incidence is related to numerous risk factors (Table 1). The most important risk factors are obesity, impaired wound healing of the laparotomy wound, malnutrition and tobacco smoking. Regarding the multifactorial pathogenesis of the disease local tissue ischemia is one of the most important risk factors. This causes weakness of the fascia and finally incisional hernia [4,5]. In addition, there are more rare causes, such as immunosuppression, diseases of the collagen metabolism and connective tissue diseases (e.g. patients with aneurysms, Ehlers-Danlos-syndrome). Any factors which are characterized by a persistent or frequent high intra-abdominal pressure (e.g. chronic cough) contribute to the development of an incisional hernia. An important risk factor is the surgeon her/himself, i.e. the quality of the abdominal closure and this is not sufficiently considered in the scientific literature. The pathogenesis of an incisional hernia is in general multifactorial.